Surgical morbidity and oncologic results after concurrent chemoradiation therapy for advanced cervical cancer. Issue 2 (24th January 2014) - Sun, Li; Sheng, Xiugui; Jiang, Jingyan; Li, Xinglan; Liu, Naifu; Liu, Yi; Zhang, Tingting; Li, Dapeng; Zhang, Xiaoling; Wei, Ping
Abstract: Objective: To evaluate the surgical morbidity and oncologic results after concurrent chemoradiotherapy (CCRT) followed by completion surgery for advanced cervical carcinoma. Methods: The present retrospective analysis included 192 patients with advanced cervical cancer (stage IIB–IVA) treated with CCRT followed by surgery and 186 control patients without completion surgery. Disease‐free and overall survival rates were compared. Results: Of the patients who underwent surgery, 27 (14.1%) had pathologic evidence of residual disease; the local control rate with CCRT was 85.9%. After a median follow‐up period of 190 months, 32 (16.7%) patients who underwent completion surgery had a recurrence compared with 59 (31.7%) of those who did not. The overall survival rate among patients who underwent extrafascial hysterectomy, extended hysterectomy, or no surgery was 72.2%, 60.1%, and 45.9% at 3 years, and 53.5%, 40.7%, and 32.2% at 5 years, respectively. Conclusion: Surgery after CCRT for advanced cervical cancer enabled evaluation of the pathologic response to therapy, improved local disease control in patients with a partial pathologic response, and enhanced survival. The most appropriate surgical approach was extrafascial hysterectomy with pelvic lymph node dissection.